Vascular wall resident progenitor cells: a source for postnatal vasculogenesis - Zengin, Elvin; Chalajour, Fariba; Gehling, Ursula M; Ito, Wulf D; Treede, Hendrik; Lauke, Heidrun; Weil, Joachim; Reichenspurner, Hermann; Kilic, Nerbil; Ergün, Süleyman (Development (Cambridge), 2006)
Here, we report the existence of endothelial precursor (EPC) and stem cells in a distinct zone of the vascular wall that are capable to differentiate into mature endothelial cells, hematopoietic and local immune cells, such as macrophages. This zone has been identified to be localized between smooth muscle and adventitial layer of human adult vascular wall. It predominantly contains CD34-positive (+) but CD31-negative (-) cells, which also express VEGFR2 and TIE2. Only few cells in this zone of the vascular wall are positive for CD45. In a ring assay using the fragments of human internal thoracic artery (HITA), we show here that the CD34+ cells of the HITA-wall form capillary sprouts ex vivo and are apparently recruited for capillary formation by tumor cells. New vessels formed by these vascular wall resident EPCs express markers for angiogenically activated endothelial cells, such as CEACAM1, and also for mature endothelial cells, such as VE-cadherin or occludin. Vascular wall areas containing EPCs are found in large and middle sized arteries and veins of all organs studied here. These data suggest the existence of a ;vasculogenic zone' in the wall of adult human blood vessels, which may serve as a source for progenitor cells for postnatal vasculogenesis, contributing to tumor vascularization and local immune response.